Hubungan Kebiasaan Merokok dengan Penyakit ISPA pada Pasien di Puskesmas Mandai Kabupaten Maros - N.H, M. Tajussubky; Rijal, Syamsu; Wiriansya, Edward Pandu (Wal'afiat Hospital Journal, 2024)
This study aims to analyze the relationship between smoking habits and the incidence of Acute Respiratory Tract Infection (ARI) in patients at Puskesmas Mandai, Maros Regency. Using quantitative methods with a correlation analytic approach and cross-sectional design, data were collected from 105 respondents from September to October 2022. The results showed that most ARI patients were children under 10 years old (51.4%), with a higher prevalence in males (58.1%). In terms of smoking status, all secondary smokers (50.5%) and the majority of tertiary smokers (37.1%) experienced ARI, while only 7.6% of primary smokers experienced ARI. Statistical analysis showed a significant association between smoking and ARI incidence (p-value less than 0.05). This finding confirms that smoking, especially in the family environment, contributes significantly to the increased incidence of ARI. It is recommended that Puskesmas Mandai conduct socialization about the dangers of smoking and further research with more respondents for more specific and comprehensive results.